[Rezension von: Herrity, Kate, ca. 20./21. Jh., Sound, order and survival in prison] - Bennett, Jamie (The British journal of criminology, 2025)
The following symposium contains four reviews of Katie Herrity’s Sound, Order and Survival in Prison, winner of the 2024 British Society of Criminology’s A